Correlation Between Screen Time and Autistic Symptoms as Well as Development Quotients in Children With Autism Spectrum Disorder - Dong, Han-Yu; Wang, Bing; Li, Hong-Hua; Yue, Xiao-Jing; Jia, Fei-Yong (Frontiers in Psychiatry, 2021)
Background: Electronic screen media play an increasingly vital role in children’s entertainment; however, excessive screen time may negatively influence child development. The purpose of this study was to investigate the relationship between the screen time of children with autism spectrum disorder (ASD) and their autistic symptoms and development quotients (DQs). Methods: We compared the screen time of 101 children with ASD and 57 typically developing (TD) children. Then, we performed a correlation analysis to determine the correlations between the screen time and the ASD-related scale scores and developmental quotients of the Gesell Developmental Schedules (GDS) of ASD children. We further divided the ASD group into subgroups according to the screen time and age and then separately conducted the above correlation analyses by subgroup. Result: The results showed that the screen time of the children with ASD was longer than that of the TD children (3.34±2.64 h vs. 0.91±0.93 h). The screen time of the children with ASD was positively correlated with the Childhood Autism Rating Scale (CARS) score (r=0.242, P=0.021) and “taste, smell and touch” item of CARS(r=0.304, P=0.005), and negatively correlated with the language DQ of the GDS (r=-0.236, P=0.047). The subgroup analysis showed that in the longer screen time subgroup of ASD children, the screen time was positively correlated with the CARS score (r=0.355, P=0.026) and negatively correlated with the DQs of all domains of the GDS (P<0.05). In addition, in the younger age group of ASD children, the screen time was positively correlated with the CARS score (r=0.314, P=0.021) and negatively correlated with the DQs of all domains of the GDS, except for the personal-social behavior domain (P<0.05). Conclusion: Compared with TD children, children with ASD have a longer screen time. The screen time is related to autism-like symptoms and the DQs of children with ASD. The longer the screen time, the more severe the symptoms of ASD (especially sensory symptoms), and the more obvious the developmental delay, especially in ASD children with a longer screen time and younger age, particularly in the language domain.